Development of salinity intrusion model (Munaf Q. 2019) In the Shatt Al-Arab River - Albattat, Munaf Q.; Khalid, Emaan T.; Al-Muhyi, Abdul Haleem A.; AL-Mosuwi, Waleed H. (Mesopotamian Journal of Marine Sciences, 2023)
Mathematical model (Munaf Q. 2019) was developed to predict the intrusion of salt into the Shatt Al-Arab River, which addresses the problem of the difficulty of measurements and prediction of the level of salinity along the Shatt Al-Arab River during the measurement period and in a very short time, where it is possible to identify the level of salinity along the Shatt Al-Arab River when it changes at the estuary. In this article, a mathematical model was used with an automatic computing system to predict the penetration of the salt intrusion into the Shatt Al-Arab, based on the development of a previous mathematical model. The results obtained through the application of the model showed that there is a great convergence between the results at a high level and at most of the stations under study (Al-Fadaqhiyah, Seyhan, Basrah, Al-Hartha) for the field-measured values with the theoretical values respectively, as follows: 27-26 ppt., 2.6-2.9 ppt., 1.85-1.96 ppt., 0.86-0.92 ppt., when the flow is 50m3/sec. When the flow is 5m3/sec, the results are as follows: 30.4-30.2 ppt., 25.3-25.1 ppt., 11.4-12.6 ppt., 1.50-1.97 ppt., Therefore the adoption of this mathematical model can be enhanced to predict the penetration of the salt as a result of any situation that may occur at any time along the Shatt Al-Arab River. The reason for using mathematical models is because it is an easy, cheap and fast way of obtaining the desired results to address some of the problems that occur for many reasons, the most important of which are direct events that may occur as a result of a sudden change in the variables dependent on them.